Should TCAR be accepted as the standard of care in carotid revascularization? - Jeffrey Jim (Annals of Vascular Surgery - Brief Reports and Innovations, 2024)
In this article, the author provides a perspective on the changing landscape for carotid interventions in the United States. The efficacy and real-world effectiveness of transcarotid artery revascularization (TCAR) is discussed to evaluate if TCAR should be accepted as the “standard of care” in carotid revascularization.